The impact of human development on cigarettes consumption in Malaysia - Fallahi, Mahdi; Mohamed Nor, Norashidah; Bui, Wency Kher Thinng (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
This paper estimates the impact of human development indicators on cigarette consumption in Malaysia from 1980 to 2012. To determine the long run relationship among the variables, ARDL bound testing approach is applied since the tested variables are a mixed of I(0) and I(1). Results show that life expectancy, -16.3828 is negatively related and highly significant in determining the cigarette consumption in Malaysia. Even though the other human development indicators are insignificant in this study, an increase in the level of life expectancy is indirectly due to better living standard and improved education. This study has an interesting implication for Malaysia’s policy in controlling cigarettes consumption. Higher taxation on cigarettes may not the only effective policy, but greater emphasis on factors that lead to improvement in life expectancy will likely reduce cigarette consumption in Malaysia.